Pemanfaatan Limbah Sayur dan Kotoran Sapi Sebagai Sumber Energi Terbarukan - Mukasi Wahyu Kurniawati; Arsita Nur Rizkia Putri; Choirunnisa Firdaus Ivana (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Waste’s dynamic problem will always be present in humans life and even get increasing each day. Waste generated from various kind of human activities and it will cause serious problem if it is not handled properly. One among many waste types which mostly produced from humans daily activities is organic waste and the concrete example is vegetable trash. Vegetable trash generated in large amount everyday that the treatment of this trash is important to be carried out. Also, vegetable trash is a source of biomass which can be converted into renewable energy source, that is biogas. This research aims to collected literature references (review) of vegetable trash conversion into biogas by adding with cow dung and draw conclusion about optimum composition of mixture of cow dung and vegetable trash which obtain highest methane gas (CH4) concentration. Cow dung is known as potential biogas raw material for its high cellulose content after digested in cow’s stomach that its is easier broken down by methane composing bacteria in methanogenenis process to produce methane gas (CH4). The variables used in this research are mass ratio between cow dung (KS) and vegetable waste (SS) variation of 100:0; 75:25; 50:50; 25:75; and 0:100 with addition of EM4. Literature review give conclusion that optimum composition mixture in biogas production process is 70% cow dung and 30% vegetable trash.